Study of Bond Properties of Steel Rebars with Recycled Aggregate Concrete. Experimental Testing - Rafi, M.M. (Проблемы прочности, 2018)
Recycling of concrete can provide an effective solution for waste management. This study investigates the interfacial bond stress versus slip response of steel bars embedded in recycled aggregate concrete. The bond tests were conducted using concentric pullout specimens. The specimens made from natural aggregate concrete were used as control specimens. Three rebar diameters, two rebar types (hot-rolled deformed and cold-twisted ribbed), and three levels of replacement of recycled aggregates (RA) were considered. The bar embedment length was taken as 5 times the bar diameter. The 12 mm-diameter bar exhibited the highest interfacial bond strength, which decreased with the bar diameter. The bond behavior of bars was nearly unaffected by the concrete type for the levels of RA replacement considered. The cold-twisted ribbed bars demonstrated a stiffer post-peak interfacial bond stress-slip response, as compared to hot-rolled deformed bars.